2018
DOI: 10.3390/rs10020324
|View full text |Cite
|
Sign up to set email alerts
|

Combining GPS, BeiDou, and Galileo Satellite Systems for Time and Frequency Transfer Based on Carrier Phase Observations

Abstract: Abstract:The carrier-phase (CP) technique based on the Global Navigation Satellite System (GNSS) has proved to be a useful spatial tool for remote and precise time transfer. In order to improve the robustness and stability of the time transfer solution for a time link, a new CP approach based on a combination of GPS, BeiDou (BDS), and Galileo satellite systems is proposed in this study. The mathematical model for the obtained unique time transfer solution is discussed. Three GNSS stations that can track GPS, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…As the two external time and frequency references at the ends of one link were real‐time free‐running and varied rapidly during the time transfer experiment, it was difficult to adopt a constant for the performance assessment. In the area of time and frequency transfer, a smooth result is employed to act as a time and frequency criterion [29, 30]. In this study, the Kalman filter for stochastic linear discrete systems was employed to smooth the original clock difference series, and the corresponding root mean square value for the smoothing result was used to assess the noise of time transfer performance.…”
Section: Resultsmentioning
confidence: 99%
“…As the two external time and frequency references at the ends of one link were real‐time free‐running and varied rapidly during the time transfer experiment, it was difficult to adopt a constant for the performance assessment. In the area of time and frequency transfer, a smooth result is employed to act as a time and frequency criterion [29, 30]. In this study, the Kalman filter for stochastic linear discrete systems was employed to smooth the original clock difference series, and the corresponding root mean square value for the smoothing result was used to assess the noise of time transfer performance.…”
Section: Resultsmentioning
confidence: 99%
“…The combined observation equation using GPS/BDS/Galileo measurements can therefore be expressed as [ 18 ]: where the superscripts , , and represent the GPS, BDS, and Galileo satellite systems, respectively. The subscript denotes a single satellite.…”
Section: Observation Equation Of Multi-gnss Cp Time Transfermentioning
confidence: 99%
“…This provides the opportunity to combine the three code-division multiple access (CDMA) satellite constellations (i.e., GPS, Galileo and BDS) for precise time and frequency transfer. By increasing the number of available satellites and improving the time dilution of precision, the time transfer solution was determined by combining the three CDMA GNSS constellations, which outperformed single GNSS solutions [ 18 ]. However, the quality of orbit and satellite clock products and pseudo-range observation accuracy of Galileo and BDS differ from those of GPS [ 19 ], and it is therefore inappropriate to treat them equally as has been done in previous studies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STD of Galileo-only PPP was improved by 51.4 and 47.6%, respectively, with the troposphere zenith delay constraint and the station coordinates constraint. Moreover, multi-GNSS PPP time transfer was investigated by Zhang et al [14]. The results showed that multi-GNSS time transfer outperformed single GNSS.…”
Section: Introductionmentioning
confidence: 99%